Strategi Pemasaran Adaptif UMKM Bidang Agribisnis Pada Lanskap Digital di CV. Seleksi Alam Muria - Wahid Nur Fajri; Muhamad Imanuddin; Heny Alpandari; Winda Widyastuti; Asti Nur Afifah (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2025)
The large Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, contributing 61% of the Gross Domestic Product (GDP), employing approximately 66 million business owners, and absorbing 97% of the workforce. MSMEs face various challenges, including branding, innovation, digital literacy, and licensing. Research on MSMEs is crucial for poverty reduction, especially in developing countries. CV Seleksi Alam Muria is one of the MSMEs in Kudus that produces various processed products from the parijoto plant, known for its health benefits. Utilizing a digital approach, this MSME aims to enhance its marketing performance, refine its strategies, and pinpoint its business strengths and weaknesses. This study analyzes the effectiveness of CV. Seleksi Alam Muria's marketing strategy in developing processed parijoto fruit products as a local flagship product of Kudus Regency. The qualitative descriptive method involves identifying internal and external factors and conducting a SWOT analysis. Using a descriptive approach and marketing mix analysis, as well as SWOT and SOSTAC, the study found that the company has successfully diversified its product line, set varied prices, implemented strategic distribution, and conducted online and offline promotions. The economic value-added reached IDR 64,833/kg, with a profitability of 35.11%, and a distribution network in seven cities. Although the marketing strategy was effective, challenges remained, including price increases and limited public awareness. Recommendations for development include market education, branding enhancement, and digital expansion.